Alzheimer's Disease: A Review from the Pathophysiology to Diagnosis, New Perspectives for Pharmacological Treatment - dos Santos Picanco, Leide C.; Ozela, Priscilla F.; de Fatima de Brito Brito, Maiara; Pinheiro, Abraao A.; Padilha, Elias C.; Braga, Francinaldo S.; de Paula da Silva, Carlos H. T.; dos Santos, Cleydson Breno Rodrigues; Rosa, Joaquín M.C.; da Silva Hage-Melim, Lorane Izabel (Current Medicinal Chemistry, 2018)
Dementia is characterized by the impairment of cognition and behavior of people over 65 years. Alzheimer's disease (AD) is the most prevalent neurodegenerative disorder in the world, as approximately 47 million people are affected by this disease and the tendency is that this number will increase to 62% by 2030. Two microscopic features assist in the characterization of the disease, the amyloid plaques and neurofibrillary agglomerates. All these factors are responsible for the slow and gradual deterioration of memory that affect language, personality or cognitive control. For the AD diagnosis, neuropsychological tests are performed in different spheres of cognitive functions but since not all cognitive functions may be affected, cerebrospinal fluid biomarkers are used along with these tests. To date, cholinesterase inhibitors are used as treatment, they are the only drugs that have shown significant improvements in the cognitive functions of AD patients. Despite the proven effectiveness of cholinesterase inhibitors, an AD carrier, even while being treated, is continually subjected to progressive degeneration of the neuronal tissue. For this reason, other biochemical pathways associated with the pathophysiology of AD have been explored as alternatives to the treatment of this condition such as inhibition of β-secretase and glycogen synthase kinase-3β. The present study aims to conduct a review of the epidemiology, pathophysiology, symptoms, diagnosis and treatment of Alzheimer's disease, emphasizing the research and development of new therapeutic approaches.
Keywords: treatment